The Republican Right since 1945 - Reinhard, David W., 1952- (Book collections on Project MUSE., 1983)
In 1981, a Right Wing Republican at long last resided in the White House, presiding over what may prove to be the most fundamental restructuring of American political life since the days of Franklin D. Roosevelt. Fortunately, The Republican Right since 1945 now provides us with the necessary historical understanding of conservative Republicans. David Reinhard's dispassionate yet lively book recounts the Republican Right's political struggles from the death of FDR in 1945 to the inauguration of Ronald Reagan. Younger readers will discover that Right Wing Republicans are older than Ronald Reagan.